MEMBACA NOVEL ‘NTAIDU KARYA MUSLIM BURMAT: PEMAHAMAN LINTAS BUDAYA (Reading Novel ‘Ntaidu’ Written by Muslim Burmat: Cross Cultural Understanding Research) - Saksono Prijanto (Balai Bahasa Sulawesi Selatan, 2014)
Reading literature of other nations is a process of intercultural learning (cross-cultural learning) so we are open to different cultures and values of a particular nation. These values play a role in the formation of the character of a cultural group, even the character of a nation. Through a cross-cultural approach to novel Ntaidu” worked by Muslim Burmat, here the thought process is expected to unfold Brunei society, whether in relation to the concept of Malay and Islamic concepts that they believe. The essence of the issue in the novel ‘Ntaidu is how leaders are able to perform the duties and functions of leadership for the progress of the village community. The issue that may arise in the future not only to droughts, but rather how they are able to educate the villagers to meet a better life. The way that we do it is not easy, even quite difficult. However, based on the understanding that the essence of the literary work and the multi-interpretation and multi-meaning, our understanding of the literary work can still be considered valid